New Heuristics and exact algorithms for the planted DNA (l, d)-Motif finding problem - JULIETA, NABOS (Archīum Ateneo, 2016)
This study explored some approaches that can improve algorithms for finding (l,d)-motifs in DNA sequences. Two new exact algorithms, EMS-PG and EMS-GT that employ pattern-based approach and instance-based approach, respectively, were developed. Number map